2022
DOI: 10.3390/en15238968
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Gas Production and Reservoir Stability during CO2 Exchange in Natural Gas Hydrate Reservoir

Abstract: The prediction of gas productivity and reservoir stability of natural gas hydrate (NGH) reservoirs plays a vital role in the exploitation of NGH. In this study, we developed a THMC (thermal-hydrodynamic-mechanical-chemical) numerical model for the simulation of gas production behavior and the reservoir response. The model can describe the phase change, multiphase flow in porous media, heat transfer, and deformation behavior during the exploitation of NGH reservoirs. Two different production scenarios were empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…23,24 Among them, the CMG-STARS model was adopted in this study, which can account for three phases (gas phase, liquid phase, and hydrate phase) and five mass components (CH 4 , CO 2 , water, CH 4 hydrate, and CO 2 hydrate) to simulate hydrate formation and dissociation. 25 The hydrate phase consisted of CO 2 hydrate and CH 4 hydrate, which were immobile solids. Considering the water and gas two-phase flow in porous media during the dissociation of hydrate, the mass conservation equations of CH 4 , CO 2 , water, and hydrate components can be represented as…”
Section: Mathematical and Numerical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Among them, the CMG-STARS model was adopted in this study, which can account for three phases (gas phase, liquid phase, and hydrate phase) and five mass components (CH 4 , CO 2 , water, CH 4 hydrate, and CO 2 hydrate) to simulate hydrate formation and dissociation. 25 The hydrate phase consisted of CO 2 hydrate and CH 4 hydrate, which were immobile solids. Considering the water and gas two-phase flow in porous media during the dissociation of hydrate, the mass conservation equations of CH 4 , CO 2 , water, and hydrate components can be represented as…”
Section: Mathematical and Numerical Modelingmentioning
confidence: 99%
“…Several numerical simulators have been developed for hydrate exploitation, and their reliability has been verified by international code comparison. , Among them, the CMG-STARS model was adopted in this study, which can account for three phases (gas phase, liquid phase, and hydrate phase) and five mass components (CH 4 , CO 2 , water, CH 4 hydrate, and CO 2 hydrate) to simulate hydrate formation and dissociation . The hydrate phase consisted of CO 2 hydrate and CH 4 hydrate, which were immobile solids.…”
Section: Mathematical and Numerical Modelingmentioning
confidence: 99%
“…With the same saturation, the increased OCR enhances the resistance of HBS to deformation, whose initial elasticity modulus increases with the OCR increasing, and related studies are shown in Table . The mechanisms of OCR effects on HBS are mainly reflected in 1) the increase of OCR breaks the cement structure of HBS, the hydrate attached to the surface of the particle is shed and fills the adjacent pores, making the density of HBS increase, so it affects the shearing strength of HBS; 2) the increase of OCR makes sediment particles arranged more tightly, and the shearing process can inhibit the sliding, rotation, and rearrangement behavior of particles significantly, which improves the initial elastic modulus and shearing strength of HBS, and prohibits the volume deformation.…”
Section: Triaxial Shear Testmentioning
confidence: 99%
“…Natural gas hydrate (NGH) is widely distributed across the world. NGH has advantages of large reserves and high energy density, and no toxic and harmful gases will be produced after combustion, which has attracted scientists from all over the world to pay great attention to this kind of energy. …”
Section: Introductionmentioning
confidence: 99%